2021
DOI: 10.1001/jama.2021.5199
|View full text |Cite
|
Sign up to set email alerts
|

Excess Deaths From COVID-19 and Other Causes in the US, March 1, 2020, to January 2, 2021

Abstract: The funders had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication. Disclaimer:The analyses described are the responsibility of the authors and do not necessarily reflect the views or policies of the US Department of Health and Human Services. The mention of trade names, commercial products, or organizations does not imply endorsement by the US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
243
2
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(261 citation statements)
references
References 2 publications
11
243
2
5
Order By: Relevance
“… 8 Studies have found an even larger number of excess deaths during the pandemic, inflated by undocumented deaths from covid-19 and by deaths from non-covid-19 causes resulting from disruptions by the pandemic (eg, reduced access to healthcare, economic pressures, and mental health crises). 9 10 11 12 Some racial and ethnic populations and age groups have been disproportionately affected. 13 14 15 Research on how the pandemic has affected life expectancy is only just emerging.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Studies have found an even larger number of excess deaths during the pandemic, inflated by undocumented deaths from covid-19 and by deaths from non-covid-19 causes resulting from disruptions by the pandemic (eg, reduced access to healthcare, economic pressures, and mental health crises). 9 10 11 12 Some racial and ethnic populations and age groups have been disproportionately affected. 13 14 15 Research on how the pandemic has affected life expectancy is only just emerging.…”
Section: Introductionmentioning
confidence: 99%
“…Although we would like to analyze external mortality in more detail, monthly death counts by age group are not yet available for sub-categories within external causes. Nonetheless, we were able to do some exploratory analyses based on monthly crude death rates for drug overdoses, 4 homicides, suicides, motor vehicle accidents, and unintentional injuries as a whole 5 (19). Currently, these provisional data are available only through October 31, 2020.…”
Section: Exploratory Analysis Of Sub-categories Of Mortality From External Causesmentioning
confidence: 99%
“…Depending in part on the period of coverage, prior studies have reported a 16-23% increase in excess mortality during the pandemic (2)(3)(4), but only 72-89% of those deaths can be attributed directly to COVID-19 (2)(3)(4)(5). During the period from January 26, 2020 to October 3, 2020, Americans aged 25-44 suffered the largest relative increase in excess mortality (27% peaking at nearly 50% in mid-July), whereas those aged 85 and older experienced a smaller increment (15%, but also peaking near 50% in late April) (6).…”
Section: Introductionmentioning
confidence: 99%
“…As prolonged second waves as well as third waves for the COVID-19 pandemic strike a large number of nations world-wide, effective treatment of this viral pneumonia remains by and large an unmet need [1,2]. In addition to supportive care, dexamethasone provides relief to acutely ill patients [3].…”
Section: Treating Covid-19: Current Status and Room For Passive Immunotherapymentioning
confidence: 99%